REGULATORY MAPPING AND REVIEW FOR THE PURPOSE OF ANALYSIS AND EVALUATION OF LEGISLATION WITHIN THE MINISTRY OF MARITIME AFFAIRS AND FISHERIES - Gyrisha; Trijono, Rachmat; Aminulloh, Muhammad (Fakultas Hukum Universitas Djuanda, 2024)
Regulatory reform is a priority program as stated in the strategic plan and work plan of the current Government. The urgency of regulatory reform is based on the condition of national regulations that are hyperregulated, inconsistent, disharmony (vertical and horizontal). Regulatory Mapping and Review (RMR) is an innovative tool that can be used to assess the quality of a large number of regulations. It is expected to be able to support regulatory reform programs. In RMR, the analysis and evaluation method uses qualitative and quantitative approaches. RMR can, in fact, help improve the quality of regulations within the Ministry of Maritime Affairs and Fisheries. The stages in RMR begin with an inventory, mapping and review/analysis of a large number of regulations, which outputs in the form of recommendations to the Ministry of Maritime Affairs and Fisheries in improving regulations that are considered problematic or formulating regulations that will be issued, making it easier for the Government to produce quality regulations and be effective in their implementation. On the other hand, RMR in fact supports efforts to simplify the number of regulations, so that an ideal number of regulations can be produced in accordance with needs, without conflict both vertically and horizontally and in an efficient and effective manner.